2007
DOI: 10.2190/96l8-6j35-0297-m403
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory and Depression in the Later Age: The Bump is a Turning Point

Abstract: This preliminary study integrated previous findings of the distribution of autobiographical memories in the later age according to their age of occurrence, with the overgeneral memory bias predictive of depression. Twenty-five non-demented, Israeli participants between 65-89 years of age provided autobiographical memories to 4 groups of word cues reflecting events from childhood, adolescence, adulthood and late age. Their autobiographical responses were coded for degree of specificity of mentioning people, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…A few studies use the Galton-Crovitz cueing method and Robinson word cuing technique [30, 7678, 81, 82, 86, 105, 106]. The number of word cues used to elicit memories range from 15–124 [15, 16, 74].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies use the Galton-Crovitz cueing method and Robinson word cuing technique [30, 7678, 81, 82, 86, 105, 106]. The number of word cues used to elicit memories range from 15–124 [15, 16, 74].…”
Section: Resultsmentioning
confidence: 99%
“…One study elicited personal future life stories of children, and events from those stories [60]. In studies where participants reported autobiographical events for various types of cues, retrieved memories were from personal pasts [15, 16, 30, 33, 59, 61–63, 69,74, 75, 7678, 81, 86, 89, 90, 92, 93, 96, 98, 104106, 109, 114]. The following were elicited in various studies: personal memories of adults spanning their life course, meaningful life events, life stories from across participants' life spans, lists of life events for AMs and collective memories, life-lines for both past and future events, and self-defining AMs [17, 22, 35, 66, 70, 72, 73, 91, 95, 97, 99, 102, 103, 107, 108, 110113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been less frequently reported in older samples, although some results support such lower specificity in older adults with depression (Birch & Davidson, 2007). Additionally, limitations in terms of the ability to provide specific memories for cue words related to adolescence was strongly associated with higher levels of depression in a small sample of older adults (Gidron & Alon, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…Phillips and Williams (1997) found greater overgenerality in older adults with cognitive impairment but no relation between current severity of depression and overgenerality. A limited ability to provide specific memories for cue words related to adolescence was strongly associated with higher levels of depression in a small sample of people in late adulthood (Gidron & Alon, 2007). Compared to older adults without depression, the group with depression retrieved significantly fewer specific memories; however, the latter did not differ with regard to their categoric (memories of a summary type) memory recall (Birch & Davidson, 2007).…”
Section: Introductionmentioning
confidence: 89%